2019
DOI: 10.1002/jsfa.9776
|View full text |Cite
|
Sign up to set email alerts
|

Pepper fragrant essential oil (PFEO) and functionalized MCM‐41 nanoparticles: formation, characterization, and bactericidal activity

Abstract: BACKGROUND It is well known that plant essential oils have good antimicrobial activity. However, their strong volatility and intense odor limit their application. Mesoporous silica (MCM‐41), a non‐toxic mesoporous material with excellent loading capability, is a promising delivery system for different types of food ingredients in the food industry. RESULTS In this study, we first performed component analysis of pepper fragrant essential oil (PFEO) by gas chromatography – mass spectrometry (GC–MS), then the MCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Confirmation of delayed volatilization was reported for lavender oil loaded into MSNs [487]. Jin et al [488] showed that MCM-41 modified nanoparticles enable high loading of pepper fragrant along with bactericidal activities against different microbes. Thus, the incorporation of essential oils from different herbs could be used effectively for infectious diseases [489,490] and treating biofilm [491].…”
Section: Essential Oilsmentioning
confidence: 58%
“…Confirmation of delayed volatilization was reported for lavender oil loaded into MSNs [487]. Jin et al [488] showed that MCM-41 modified nanoparticles enable high loading of pepper fragrant along with bactericidal activities against different microbes. Thus, the incorporation of essential oils from different herbs could be used effectively for infectious diseases [489,490] and treating biofilm [491].…”
Section: Essential Oilsmentioning
confidence: 58%
“…Clove essential oil (CEO) was loaded in MSN based on previous studies with slight modifications (Jin et al ., 2019). Dichloromethane (15 mL) and CEO (200 µL) were added to 50‐mL conical bottles.…”
Section: Methodsmentioning
confidence: 99%
“…Among several types of MSNPs, MCM-41 nanoparticles with a hexagonal structure and mesopores with a diameter of 2.0-6.5 nm have often been employed to encapsulate plant VOCs [112]. Jin et al synthesised MCM-41 nanoparticles with an average size of 717 nm and a zeta potential of − 43.9 mV and loaded PFEO (pepper fragrant essential oil) into the hollow MSNPs by stirring n-hexane solution containing the volatiles and nanoparticles for 24 h. PFEO laden nanoparticles demonstrated improved antimicrobial activity against foodborne bacteria compared to PFEO, e.g., the total inhibitory concentrations of the nanoformulation and free compounds against S. aureus were 20.0 and 22.5 mg/mL upon 48 h treatment, respectively [113]. Solvent immersion appeared to be the best way to load volatiles into MSNPs, as the other methods such as the melting process might result in a loss of VOCs during the loading process.…”
Section: Nanoencapsulation Systems For Carrying Plant Volatile Organimentioning
confidence: 99%
“…Mesoporous silica nanoparticle Antibacterial [7] Pepper VOCs Mesoporous silica nanoparticle Antibacterial [113] Coleus aromaticus VOCs Silver nanoparticle Antibacterial [168] Eugenia caryophyllata VOCs Chitosan nanoparticle Antifungal [143] Carvacrol Nanoemulsion Antifungal [169] Zataria multiflora VOCs Solid lipid nanoparticle Antifungal [146] Cymbopogon citratus VOCs Poly (D,L-lactide-co-glycolide) nanoparticles Antiviral [148] Artemisia arborescens VOCs Nanoliposome Antiviral [149] Santolina insularis VOCs Nanoliposome Antiviral [150] Curcuma longa & Cymbopogon citratus VOCs Chitosan-alginate nanocapsule Anticancer [151] Ocimum Gratissimum VOCs Chitosan nanoparticle Trimethyl chitosan nanoparticle Anticancer [152] Citral Bovine serum albumin nanoparticle Anticancer [154] Citrus bergamia VOCs Nanoliposome Anticancer [155] Ginger & frankincense VOCs Nanoemulsion Anticancer [157] Origanum glandulosum VOCs Sodium alginate nanocapsule, nanoemulsion Anticancer [158] Mentha spicata VOCs Nanoemulsion Anticancer [170] Citral Solid lipid nanoparticle Anticancer [171] Nigella sativa VOCs Gold nanoparticle Anticancer, antibacterial [117] fection of catfish with a very low concentration (5 µL/L) of volatiles is more environmentally safe and cost-effective [137]. The antibiofilm effects of free cinnamon oil and nanoliposomes carrying the oil were tested against MRSA by Cui et al The logarithmic value of a viable MRSA population in the biofilms treated with cinnamon oil was decreased by 1.49 times whereas those treated with cinnamon oil-loaded nanoliposomes led to the reduction of MRSA cells by 2.45 times.…”
Section: Solid Lipid Nanoparticle Nanostructured Lipid Carriermentioning
confidence: 99%